2015
DOI: 10.3402/gha.v8.26957
|View full text |Cite
|
Sign up to set email alerts
|

The experience of caregivers of people living with serious mental disorders: a study from rural Ghana

Abstract: BackgroundFamilies and friends who give care to people with mental disorders (MDs) are affected in a variety of ways and degrees. The interplay of caregiving consequences: poverty, discrimination and stigma, lack of support from others, diminished social relationships, depression, emotional trauma, and poor or interrupted sleep are associated caregiver burden.ObjectiveThe burden of care on caregivers of people living with MDs was assessed in two districts located in the middle part of Ghana. Coping strategies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
120
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(146 citation statements)
references
References 55 publications
19
120
0
7
Order By: Relevance
“…In consistent with previous research family caregivers of dementia people face several public backlashes [33]; [27]; [28]; [34]. The public backlashes include ridicule, mockery and social stigma family caregivers of dementia patient face as a result of caregiving duties.…”
Section: Social Challenges Of Family Caregiverssupporting
confidence: 85%
“…In consistent with previous research family caregivers of dementia people face several public backlashes [33]; [27]; [28]; [34]. The public backlashes include ridicule, mockery and social stigma family caregivers of dementia patient face as a result of caregiving duties.…”
Section: Social Challenges Of Family Caregiverssupporting
confidence: 85%
“…In our study caregivers in Southwestern Uganda receive emotional and instrumental support for their ailing patient with dementia from sources outside of the medical system These supports were most often obtained from one's religious community, social network, and one's own family. In a similar study in Ghana, Caregivers reported facing financial burden, social exclusion, emotional challenges , depression, and inadequate time for other social responsibilities and that the responsibilities around caregiving were mostly shared among close relatives (18). This is consistent…”
Section: Tablesupporting
confidence: 60%
“…An emerging body of research from LMICs suggests that informal caregivers in LMICs also experience emotional distress associated with managing their loved one's daily care routines and challenging behavioral symptoms (13)(14)(15). Caregiver burden and associated distress in LMICs is also compounded by lack of social support and shortage of formal specialized medical care for people with ADRD (16)(17)(18)(19). Given the projected rapid increase in ADRD prevalence in sub-Saharan Africa, enhancing support for caregivers of persons with ADRD in this region is of urgent importance (8).…”
mentioning
confidence: 99%
“…(21) The work burden, the complicated coexistence with the care receiver, and the limitation of the caregiver's time to invest in health promotion actions often end up influencing the caregiver's illness. (22) In terms of pain, the average burden of the participants who started to experience pain after the elderly had become bedridden, was significant for the domains emotional burden, personal life implications, financial burden, mechanism of effectiveness and control, and total burden score. For those caregivers who continue experiencing pain after they provide care, the mean burden is higher, significantly affecting all the domains evaluated.…”
Section: Discussionmentioning
confidence: 99%